Exploring the Role of Translation in Communicative Language Teaching or the Communicative Approach. (May 2020) - Adil, Mohammad
This study aims to investigate the perception of language teachers and their experience regarding the use of translation as a language teaching approach in Saudi Arabia. The study adopted a cross-sectional qualitative design to investigate the role of translation as a communicative approach in language teaching. Data were collected through a semi-structured interview with 20 professors and lecturers who were teaching at a university in Saudi Arabia. The interview results revealed that language translation strategy is effective in developing the necessary communicative ability among Saudi language learners. Also, the use of translation should be based on the skill set and competence level. It concludes that the judicious use of the translation should be practiced for Communicative Language Teaching.